Governing value creation in construction project: a new model. Issue 1 (4th January 2017) - Hjelmbrekke, Hallgrim; Klakegg, Ole Jonny; Lohne, Jardar
Abstract : Purpose: The purpose of this paper is to describe how the concepts of business models and project governance can enhance value creation in building projects. Design/methodology/approach: Based on theory derived from management literature, the authors outline a framework combining a project's business case and governance functions with the business model of the design team. This was tested in two major projects and evaluated in three expert workshops. Findings: The research reveals that the business model of the design team focus on efficiency rather than on the client's strategic objectives. This entails a need for project governance functions. The framework presented shows promising capability of aligning the project with client strategy. The authors believe there is significant value in transferring these ideas and knowledge across national boundaries. Practical implications: The research identifies a gap between business objectives and outcome. The value creation approach in the client organisation diminishes into the way project governance is implemented in some projects. The conceptual framework provides the industry with a new tool for improving its knowledge and practice. Originality/value: First governance model derived from strategy theory that combines strategy and governance in one holistic model.